2022
DOI: 10.3390/children9071026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Pediatric Drugs and Brushing on the Color Stability of Esthetic Restorative Materials Used in Pediatric Dentistry: An In Vitro Study

Abstract: The aim of the current study is to observe how different pediatric drugs and tooth brushing affect the color stability of different esthetic restorative materials. Three restorative materials (composite, compomer, and glass ionomer cement (GIC)) were each used to produce 72 specimens (10 mm × 2 mm). The specimens were divided into six groups and immersed in distilled water and five different pediatric drugs (amoxicillin, ibuprofen, ventolin, paracetamol, and multivitamins). Each group was divided into two subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Almutairi et al also included multivitamins in their study, in which they used popular pediatric fluid medications. They found that GIC (glass ionomer cement) was less color stable [ 9 ]. Similarly, the giomer was the most discolored material in the present study due to its glass ionomer content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almutairi et al also included multivitamins in their study, in which they used popular pediatric fluid medications. They found that GIC (glass ionomer cement) was less color stable [ 9 ]. Similarly, the giomer was the most discolored material in the present study due to its glass ionomer content.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these vitamin supplements can be an extrinsic source and may be responsible for color change in resin composite Materials 2024, 17, 1040 2 of 12 restorations. Researchers have conducted a few studies to evaluate the changes in surface roughness [8] and discoloration [8,9] of dental resin composite materials caused by vitamin syrups. Changes in the properties of resin composites, such as roughness and color, may affect the lifespan of these materials and increase patients' esthetic concerns [10].…”
Section: Introductionmentioning
confidence: 99%
“…This value is determined with the ∆E ab and ∆E 00 values, which are calculated by using the CIELab and CIEDE2000 formulas. The ∆E ab values, which represent the distance between the color coordinates (L*, a*, and b*) [35], are used in most studies in pediatric dentistry [1,2,11,26,29,34,49,50]. Thus, to compare the results with the relevant studies, the mean ∆E ab values of the experimental groups were determined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the specimens were cleaned in distilled water by using an ultrasonic device. The specimens were numbered and kept in distilled water in the incubator at 37 • C for 24 h to complete the polymerization [2,11,33].…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Some studies have stated that antiepileptic drugs (Sodium Valproate and Tegrotol) have negatively affected dental fillings [12,14,15]. Different studies have been conducted on whether pediatric medications frequently used in children affect the color of aesthetic fillings [16,17]. However, no study has assessed the effect of only antiepileptic drug groups and brushing on discoloration of restorative materials.…”
Section: Introductionmentioning
confidence: 99%